HUBUNGAN POLA MAKAN DENGAN RISIKO GASTRITIS PADA REMAJA - Fista Juliani; Herlina Herlina; Sofiana Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Adolescents tend to have a frequency of irregular eating, instant lifestyles and wrong eating patterns where adolescents like instant foods (fast food) that can cause gastritis. Symptoms in adolescents that often arise are pain and nausea. The aim of research is to know the relationship of eating pattern with the risk of gastritis in adolescents. The research design used is